Effect of Soyflour (Glycine max L.) Hepatoprotector Activity on Liver MDA Level in Male Wistar Rat Induced by Diazinon - Sofi Aliyatul Himah; Desie Dwi Wisudanti; Heni Fatmawati (Journal of Agromedicine and Medical Sciences, 2018)
Diazinon is metabolized in liver becomes diazoxon, an active metabolite form that can cause free radical raisingthat leads to lipid peroxidation. The result of lipid peroxidation is MDA. Soyflour has higher isoflavones than theother processed food of Glycine max L.This isoflavones donate its electron and hydrogen atom in lipidperoxidation so it can block the lipid peroxidation. The aim of this experiment is to investigate the effect of soyflour on MDA hepar level increase of male wistar rat induced by diazinon. The sample are divided into 5 groupswhich are Kn, K(-) group induced by diazinon 40mg/kgBW, K1, K2, K3 group given with soy flour 10%, 15%, and20% orally, then induced by diazinon 40 mg/kgBW. MDA liver measured on the day 34th with MDA-TBAmethode which has pink colour and measured by spectrofotometer. Average of liver MDA levels is Kn 6,35μg/mL; K(-) 9,23 μg/mL; K1 8,85 μg/mL; K2 7,88 μg/mL; K3 7,04 μg/mL. One way ANOVA and Post hoc LSDshowed significantly different (p<0,05). Pearson correlation showed strong negative correlation. Keywords: Diazinon, Diazoxon, MDA, Soyflour, Glycine max L., antioxidant